2021
DOI: 10.1161/jaha.120.018206
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Left Ventricular Scar Using Cardiac Magnetic Resonance in Athletes With Apparently Idiopathic Ventricular Arrhythmias

Abstract: Background In athletes with ventricular arrhythmias (VA) and otherwise unremarkable clinical findings, cardiac magnetic resonance (CMR) may reveal concealed pathological substrates. The aim of this multicenter study was to evaluate which VA characteristics predicted CMR abnormalities. Methods and Results We enrolled 251 consecutive competitive athletes (74% males, median age 25 [17‐39] years) who underwent CMR for evaluation of VA. We inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…Although one study showed that the PVC burden was higher in patients with abnormal CMR findings [ 7 ], our study confirmed previous observations that the number of PVCs was not predictive of pathological CMR findings [ 5 , 29 ]. On the contrary, one study in athletes found that those with no scarring on LGE imaging had a higher PVC burden than athletes with LGE findings [ 30 ]. This may be explained by the fact that ectopic foci located in the outflow tract of the ventricles may give rise to very frequent PVCs [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although one study showed that the PVC burden was higher in patients with abnormal CMR findings [ 7 ], our study confirmed previous observations that the number of PVCs was not predictive of pathological CMR findings [ 5 , 29 ]. On the contrary, one study in athletes found that those with no scarring on LGE imaging had a higher PVC burden than athletes with LGE findings [ 30 ]. This may be explained by the fact that ectopic foci located in the outflow tract of the ventricles may give rise to very frequent PVCs [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The scar often showed a subepicardial/midmyocardial distribution (non-ischemic) and was more likely when PVBs depicted an RBBB-like pattern or multiple morphologies, or when non-sustained VT was recorded during exercise testing. Conversely, a high number of PVBs (>3300/day) predicted a normal CMR (Figure 5) [23].…”
Section: Relationship Between Pvb Features and Nlvs Revealed By Cmrmentioning
confidence: 99%
“…Biventricular myocardial fibrosis was found in the postmortem examination of a famous Italian footballer who died suddenly during a competition [20]. No matter the cause, a NLVS should be regarded as clinically significant because it is a possible substrate for macro-reentrant VT [21][22][23][24].…”
Section: Substrates Of Pvbs In Athletesmentioning
confidence: 99%
See 1 more Smart Citation
“…The appearance of PVCs or even VT during exercise is more frequent in individuals with SHD, fact that implies a worse prognosis and a need for deeper evaluation. In a study with otherwise apparently healthy athletes, those with repetitive PVCs during exercise were found to represent a high-risk subgroup and the presence of exercise-induced non-sustained polymorphic VT was associated with a probability of an underlying LV scar of 67% (22,23). Anyway, patients with idiopathic PVCs who develop monomorphic VT during exercise testing are still considered to have good prognosis, but a thorough investigation is necessary to ensure its benign nature (24).…”
Section: Clinical Presentationmentioning
confidence: 99%